2012
DOI: 10.1111/ijfs.12028
|View full text |Cite
|
Sign up to set email alerts
|

Effect of heating fatty fish: Baltic herring (Clupea harengus membras), European sprat (Sprattus sprattus) and rainbow trout (Oncorhynchus mykiss) on lipid oxidation and contents of eicosapentaenoic and docosahexaenoic acids

Abstract: Summary In this study, analyses were carried out to establish the impact of heating three species of fatty fish: trouts, herrings and sprats, on the lipids oxidation and on contents of eicosapentaenoic (EPA) and docosahexaenoic (DHA) acids. The comminuted fish tissue was heated at restricted access of oxygen at temperature of 60, 100 and 160 °C for 15–120 min. Lipids, extracted with the Bligh‐Dyer method, were determined for peroxide value (PV) and anisidine value (AV). The Fatty acid methyl esters were prepar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 34 publications
1
15
0
Order By: Relevance
“…However, the signifi cant difference was found only for the DHA acid. Domiszewski [2013] revealed that the heating of trout and sprats minced tissue at temperatures of 60, 100 and 160°C, even for 1-2 h, did not evoke losses, either in EPA or in DHA content, but in the case of herring, the heat treatment applied for 90-120 min contributed to 20-25% decrease in the contents of these fatty acids.…”
Section: Resultsmentioning
confidence: 94%
“…However, the signifi cant difference was found only for the DHA acid. Domiszewski [2013] revealed that the heating of trout and sprats minced tissue at temperatures of 60, 100 and 160°C, even for 1-2 h, did not evoke losses, either in EPA or in DHA content, but in the case of herring, the heat treatment applied for 90-120 min contributed to 20-25% decrease in the contents of these fatty acids.…”
Section: Resultsmentioning
confidence: 94%
“…High retention of DHA and EPA contents in cooked fish, such as those observed in grilled and pan-fried saury in this study, has been accredited to the protective effect of endogenous antioxidants against oxidation (Regulska-Ilow and Ilow 2002;Al-Saghir and others 2004;Gladyshev and others 2006;Larsen and others 2010;Domiszewski 2013). Therefore, the antioxidant activity of cooked saury was assessed for potential associations with DHA and EPA content.…”
Section: Effect Of Cooking On Antioxidant Activity Of Saurymentioning
confidence: 81%
“…Cooking has been reported to change the DHA and EPA contents of fish (García‐Arias and others ; Larsen and others ; Turhan and others ; Zhang and others ; Hosseini and others ), changes of which appear to be species dependent (Ansorena and others ; Domiszewski ; Schneedorferová and others ). Tamari and others () reported that the grilling of Pacific saury fillets decreased DHA and EPA contents by 67% and 72%, respectively, while deep‐frying decreased contents by 77% and 81%, respectively.…”
Section: Introductionmentioning
confidence: 99%
“…According to Castro et al and Webber et al, cooking did not affect the fatty acid composition of fish flesh [31,32]. On the other hand, the losses in EPA and DHA during long-term heating of herring at temperature of 100 and 160 °C were observed by Domiszewski [33]. Karlsdottir et al also reported that the initial quality of a raw material before cooking is critical with regard to change in fatty acid composition of cooked fish products [34].…”
Section: Discussionmentioning
confidence: 96%